2017
DOI: 10.18203/2394-6040.ijcmph20173865
|View full text |Cite
|
Sign up to set email alerts
|

A study on evaluation of health and nutrition day in urban slums of Berhampur, Odisha

Abstract: Background: Urban health and nutrition day (UHND) serves as a common platform to deliver maternal, child health care, nutrition and WASH services to the urban poor population. This study was formulated with an objective to study the availability of resources at the UHND, to assess the services provided and to determine the satisfaction by the beneficiaries.Methods: A cross sectional study was conducted in urban slum of Berhampur from November 2016 to January 2017 and 10% of UHND sessions were observed. Data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…[ 22 ] observed that 27% of slums all over India had no garbage disposal facility and revealed that majority of the slum population disposed their liquid wastes (68.3%) and solid waste (59.8%) haphazardly. [ 22 , 23 ] Similar results have been found in this study which revealed distorted ways of waste disposal among slum households. About 69.8% reported that they disposed the solid wastes at the community dumping spot set by the BMC, while 83% reportedly disposed liquid wastes in the open drainage system of kutcha origin.…”
Section: Discussionsupporting
confidence: 87%
“…[ 22 ] observed that 27% of slums all over India had no garbage disposal facility and revealed that majority of the slum population disposed their liquid wastes (68.3%) and solid waste (59.8%) haphazardly. [ 22 , 23 ] Similar results have been found in this study which revealed distorted ways of waste disposal among slum households. About 69.8% reported that they disposed the solid wastes at the community dumping spot set by the BMC, while 83% reportedly disposed liquid wastes in the open drainage system of kutcha origin.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, papers on growth monitoring and counselling often look at the availability of infrastructure at AWCs or health centres, but more specifically measure for availability of growth charts (Haider et al 2014) or weighing scales (Tripathy et al 2017).…”
Section: Programme Levelmentioning
confidence: 99%